Ways Out of Poverty : Diffusing Best Practices and Creating Capabilities--Perspectives on Policies for Poverty Reduction - Klein, Michael (World Bank, Washington, DC, 2014)
Fundamentally, poverty reduction is about bringing growth processes to poor areas. Because poor areas can benefit from technical and organizational innovations made elsewhere in the world, it is possible today to create productive jobs faster and in greater quantity than ever before. The puzzle is what helps spread such "best practices." Saving, investment, education, resources, and new technology are all needed-and fairly easy to obtain. What is hard to obtain are the institutions that allow these factors of production to be combined and translated into productive job creation. Firms are the key vehicles that spread best practices and productive jobs to areas where poor people live. Because we can never be sure which firm will be successful, it is necessary that new firms can enter markets, that substandard firms are allowed to fail, and that good firms face few barriers to growth. This is the definition of competition, and competition is what selects good firms and thus drives the spread of best practice and productive jobs. Governments need to provide the framework in which capable firms can emerge. Yet, the right mix of state activity and how it best interacts with firms are not fully understood. Some selection mechanism, which allows for policy experiments and selects successful ones, is valuable for national, provincial, and local governments. Thus competition among jurisdictions and firms is an integral part of dynamic social systems that hold promise for creating wealth and ending poverty.